2001
DOI: 10.1002/1521-4109(200102)13:2<155::aid-elan155>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Oxidation of Nitrite at a Molybdenum Oxide Layer

Abstract: The anodic oxidation of nitrite at a glassy carbon surface modified by a molybdenum oxide layer electrochemically deposited is discussed. The results demonstrated that at certain thickness values the film is permeable to small substrates like iodide and nitrite. On the other hand, at anhydrous films (prepared by vacuum evaporation) no electrochemical response for nitrite was observed in experiments performed in a CH3CN solution, confirming the relationship between the porosity of the film and its water content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 36 publications
0
24
0
4
Order By: Relevance
“…In order to avoid such limitations, several studies have reported on the use of chemically modified electrodes with phthalocyanines, porphyrins, hemoglobin, and myoglobin for the reduction of nitrite [150,276,[441][442][443][444][445][446][447]. In spite of the fact that the anodic electrochemical determination of this anion offers several advantages, such as no interference from nitrate and from molecular oxygen, there are very few reports related to the oxidation of nitrite [277,448].…”
Section: Catalytic Properties Of Mpcs In Electrochemical Oxidation Ofmentioning
confidence: 99%
“…In order to avoid such limitations, several studies have reported on the use of chemically modified electrodes with phthalocyanines, porphyrins, hemoglobin, and myoglobin for the reduction of nitrite [150,276,[441][442][443][444][445][446][447]. In spite of the fact that the anodic electrochemical determination of this anion offers several advantages, such as no interference from nitrate and from molecular oxygen, there are very few reports related to the oxidation of nitrite [277,448].…”
Section: Catalytic Properties Of Mpcs In Electrochemical Oxidation Ofmentioning
confidence: 99%
“…Obviously, this assumption is valid for reversible electrochemical systems such as the ferri/ferrocyanide couple, as previously demonstrated. On the other hand, nitrite is a well-studied anion whose irreversible anodic oxidation leads to nitrate in a 2-electron process [26], as Eq. (9) shows:…”
Section: The Use Of the Tetlc To Investigate Irreversible Systems Andmentioning
confidence: 99%
“…However, use of electrochemical [8][9][10] methods is fast increasing as they are faster, safer and precise for the nitrite analysis. Nitrite oxidation is usually favoured over reduction since interferences such as nitrate and oxygen are avoided [11,12]. Poor sensitivity often results from the oxidation of nitrite at a bare electrode, since the surface is passivated by species that may be generated in solution due to high overpotentials.…”
Section: Introductionmentioning
confidence: 99%
“…Tau, T. Nyokong / Journal of Electroanalytical Chemistry 611 (2007)[10][11][12][13][14][15][16][17][18] …”
unclassified